Inhilal talabi dar puishishi shu'arhai-yi vahdat : (Ittihadiyyahi-yi Danishjuyani Irani dar Alman va Birlinni Gharbi (Havadari Sazmani Paykar dar Rahi Azadi-yi Tabaqahi-yi Kargar))
Dissolutionism disguised behind the slogans of unity: a critique of the positions of the "Group for the Liberation of the Working Class" and the "Organisation of the Freedom Fighters of the Working Class" in the course of the National Consultative Assembly elections.